Correction: Surface passivation assisted lasing emission in the quantum dots doped cholesteric liquid crystal resonating cavity with polymer template. Issue 22 (11th March 2015) - Chen, Lin-Jer; Lee, Chia-Rong; Chu, Chung-Liang
<x xml:space="preserve">Abstract</x> Correction for 'Surface passivation assisted lasing emission in the quantum dots doped cholesteric liquid crystal resonating cavity with polymer template' by Lin-Jer Chen et al., RSC Adv., 2014, 4, 52804–52807.